Wood Use in Mongolia: From the photographs of the late 19th and early 20th centuries - Y. Konagaya; K. Suzuki (Nomadic Civilization: Historical Research, 2024)
The original version of this article was published in Japanese by the Japan-Mongolia Association in the journal “Japan and Mongolia” (Vol. 55, pp. 76–101). Permission to use photographs was obtained from the American Museum of Natural History for academic purposes only. In this version appendix (explanatory comments about travelers such as Potanin, Pozdneev, etc.), that was in the Japanese original, is omitted. In this article, the authors focused on describing wood, lumber, and logs. It is necessary to distinguish these concepts from each other. Here, timber refers to trees as a resource, as well as the area of a small forest. Wood is one of the most popular materials for manufacturing. Lumber is produced from it. Lumber is sawn and prepared wood, including firewood. They vary in shape, size, pattern, differences and physical properties (boards, logs, beams and whetstones). A log is a sawn tree, only cleared of husks. In addition, the authors would like to thank courtesy for using the photographs.